Primary fatty acid amide metabolism: conversion of fatty acids and an ethanolamine in N(18)TG(2) and SCP cells1 - Farrell, Emma K. (The American Society for Biochemistry and Molecular Biology, 2012)
Primary fatty acid amides (PFAM) are important signaling molecules in the mammalian nervous system, binding to many drug receptors and demonstrating control over sleep, locomotion, angiogenesis, and many other processes. Oleamide is the best-studied of the primary fatty acid amides, whereas the other known PFAMs are significantly less studied. Herein, quantitative assays were used to examine the endogenous amounts of a panel of PFAMs, as well as the amounts produced after incubation of mouse neuroblastoma N(18)TG(2) and sheep choroid plexus (SCP) cells with the corresponding fatty acids or N-tridecanoylethanolamine. Although five endogenous primary amides were discovered in the N(18)TG(2) and SCP cells, a different pattern of relative amounts were found between the two cell lines. Higher amounts of primary amides were found in SCP cells, and the conversion of N-tridecanoylethanolamine to tridecanamide was observed in the two cell lines. The data reported here show that the N(18)TG(2) and SCP cells are excellent model systems for the study of PFAM metabolism. Furthermore, the data support a role for the N-acylethanolamines as precursors for the PFAMs and provide valuable new kinetic results useful in modeling the metabolic flux through the pathways for PFAM biosynthesis and degradation.